Avaliação de cobre e zinco em água, sedimento e peixes do rio Apucaraninha na região da terra indígena Apucarana (Tamarana, PR) - Dornelles, Fernanda Nasser (2016)
Average concentrations (mg/kg) of copper (Cu) and zinc (Zn) were determined in water and sediment samples collected in Apucaraninha river in winter 2015 and summer 2016 at downstream sites of Indigenous Land Apucarana (Tamara - PR), depending on the potentially polluting use and occupation of the basin in the mentioned territory. They also determined the average concentrations in the species Astyanaxaltiparanae, Oligosarcusparanaense and Geophagusbrasiliensis collected by the indigenous community from their fishing routines. The variations between the concentrations of Cu and Zn were analyzed in the sediment at different sites. Variations in the concentrations of Cu and Zn were analyzed in the species A. altiparanaeamong different size classes and the sampling years (2013,2015 and 2016).The concentration of Cu in the samples of water and fish were below the detection limit of the analytical technique. In the sediment, the Cu concentrations were above the level, while the Zn proved lower level below which provides low probability of adverse effects to biota established by Resolution of the National Environmental Council (CONAMA), revealing significant variation between sampling sites. The three species of fish analyzed showed Zn concentrations above the allowable limit for fish and fishery products according to Ordinance No. 685 of 1998 of the Secretary of Health Surveillance, Ministry of Health. There were significant variations in concentrations among different size classes of A. altiparanae and decrease along of the years 2013 to 2016, which may be related to the emptying of the reservoir in 2014, which influenced the levels of this trace element in the material sedimented. Despite the Cu and Zn are micronutrients trace metals, both are present in this hydric resources at levels that attract the attention by the degree of environmental contamination of the basin. In the studied locality this exposure is worrisome because fish make up the feeding routine of the indigenous community, since the practice of fishing is very common among families, being an essentntl component of their culture and livelihood.